Antibiogram of Salmonella Spp Isolates in Kathmandu, Nepal - Gajurel, Damodar; Sharma, Rabi Prakash; Dhungana, Krishna; Neupane, Samir; Lamsal, Kamal; Karki, Prasant; Acharya, Sudikshya (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Drug resistant Salmonella spp. is endemic in several Asian countries. Nalidixic acid-resistant Salmonella enterica serovar Typhi and Salmonella enterica serovar Paratyphi A show reduced susceptibility to fluoroquinolones and have resulted in a rise in treatment failures. Over the past few decades, nalidixic acid-resistant Salmonella spp have emerged in Nepal as well. MATERIAL & METHODS: This is a retrospective study that aims to provide a more recent antibiogram of S. Typhi and S. Paratyphi A isolates in Kathmandu. Between Poush, 2071 and Ashwin, 2072 (December 16, 2014 to October 17, 2015), 186 culture positive cases of enteric fever were diagnosed at the Civil Service Hospital. Upon isolation of S. Typhi or S. Paratyphi A, antimicrobial susceptibility testing was performed with amoxicillin, azithromycin, ceftriaxone, chloramphenicol, ciprofloxacin, cotrimoxazole, nalidixic acid, ofloxacin and tetracyciline. RESULTS: This study shows a much higher frequency of nalidixic acid-resistance in Kathmandu than previously reported; 95.7% in Salmonella enterica serovar Paratyphi A and 86.5% in Salmonella enterica serovar Typhi.The rates of ciprofloxacinand ofloxacin-resistance were over 50% in both serovar. CONCLUSION: In Nepal, it is necessary to reevaluate the use of fluoroquinolone therapy and introduce feasible alternatives so as to curb treatment failures. Journal of Universal College of Medical Sciences (2017) Vol. 5, No, 2, Page: 22-25